PENGARUH GAME EDUKASI “EDUCAPLAY” TERHADAP KEMAMPUAN BERHITUNG PENGURANGAN PADA SISWA KELAS 2 SDN 211 PALEMBANG - siska; Hikmah Lestari; Mega Prasrihamni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the educational game educaplay on the students calculating ability to subtract class 2 SDN 211 Palembang. This research method uses a quantitative approach using the True Experiment type, in the form of a Posttest-Only Control Design. The data collection technique is carried out through a learning outcome tests that is given treatment and posttest. The results of the posttest data analysis show that the average experimental value of 87,14 is higjer that the control class with an average value of 42,25. The analysis technique used in this study is the t-test, in testing the hypothesis obtained a t-count value > trabel of 0,05 > 0,077, based on the independent sampel test t-test in this study obtained a sig value (2-tailled) 0,000 < 0,05, so it can be concluded that the significant value is less than 0,05,then Ho is rejected and Ha (there is influence) is sccepted. It can be concluded the effect to the educational game educaplay on students calculating ability to subtract class 2 SDN 211 Palembang.